Prognostic parameters for response to enzalutamide after docetaxel and abiraterone treatment in metastatic castration‐resistant prostate cancer patients; a possible time relation. Issue 1 (22nd September 2015) - Badrising, Sushil K.; van der Noort, Vincent; van den Eertwegh, Alfons J.M.; Hamberg, Paul; van Oort, Inge M.; van den Berg, Hendrik P.; Los, Maartje; Aarts, Maureen J.B.; Coenen, Jules L.L.M.; Gelderblom, Hans; de Jong, Igle J.; Kerver, Emile D.; et al.
Abstract : BACKGROUND: Abiraterone Acetate (AA) and Enzalutamide (Enz) are effective hormonal treatments in mCRPC patients. Retrospective studies suggested clinical cross‐resistance between Enz and AA. However, 12.8–39.1% of patients previously treated with docetaxel (Doc) and AA do respond to Enz. These responders have not been characterized. METHODS: 102 Enz treated mCRPC patients after AA and Doc treatment were included in this study. Differences in patient characteristics and previous treatment outcomes between PSA responders and non‐responders on Enz were evaluated. RESULTS: Median Progression‐Free Survival was 12.2 weeks (95%CI 11.7–14.3) and Overall Survival 43.5 weeks (95%CI 37.4–61.2). There were 26 (25%) Enz‐responders and 76 (75%) non‐responders. Significant higher percentages of Gleason scores ≥8 and PSA doubling times (PSA‐DT) <3 months were found in Enz responders than in non‐responders. The interval between end of AA and start of Enz treatment (IAE) for responders was 24.6 weeks (IQR 4.0‐48.1) and 8.9 weeks for non‐responders (IQR 3.7–25.9) (P = 0.08). In an IAE <40 days subgroup (34 patients), Enz responses were related to AA non‐responsiveness, while univariate and logistic regression analysis of baseline criteria of a subgroup of patients with an IAE≥40 (68 patients) revealed significant differences in baseline PSA levels, PSA‐DT <3 months, Gleason scores ≥8 and IAE's between Enz responders and non‐responders. CONCLUSIONS: PSA response to Enz after previous AA and Doc treatment was associated with a longer IAE, a higher Gleason score and a PSA‐DT <3 months. Identification of these patients might be of value for sequencing of treatment options. Prostate 76:32–40, 2016 . © 2015 Wiley Periodicals, Inc.